The intergenerational conversation amongst Xhosa women in Centane about contraception use over the past 50 years - Mabandla, Athini (African Studies, 2025)
To understand the culture, intergenerational beliefs, and attitudes towards contraception use among Xhosa women in Centane. This study is based on fifteen in-depth interviews with Xhosa women from Centane who identify themselves as amaGcaleka, a sub-tribe from the main tribe amaXhosa. This study used autoethnography which explores a culture's relational practices, common values, beliefs, and shared experiences to help the insiders (cultural members) and outsiders (cultural strangers) gain a deeper understanding of the culture. Thematic analyses provided two key themes: (1) AmaGcaleka culture and (2) Women's contraception. In this study I found that in Centane there is a lack of information about contraceptive use, and that the amaGcaleka women had their own traditional forms of contraception that they used before the modern contraceptives. The lack of access to contraception and cultural beliefs had an influence on the lack of conversation between the intergeneration's of mothers and daughters.